STRATEGI MANAJEMEN FARMASI UNTUK MENINGKATKAN EFISIENSI PELAYANAN DI RS R. D. KANDOU MANADO - Ardelia Emily; Endang Komara; Rinawati, Rinawati (Journal of Innovation Research and Knowledge, 2026)
An efficient pharmacy service is a crucial component of the hospital care system because it directly affects service quality and patient safety. This study aims to identify and formulate an integrated pharmacy management strategy to improve service efficiency at R. D. Kandou General Hospital Manado, focusing on inefficiencies in drug distribution flows, delays in the procurement of medicines and consumables, and limited integration between the pharmacy information system and the Electronic Medical Record (EMR). The research uses a qualitative approach with a case study design and purposive sampling of 11 informants representing pharmacy staff, medical staff, and support management. Data were collected through in-depth interviews, observation of service flows, and document review, then analyzed using thematic analysis. The findings reveal process waste (duplicate documentation, manual queuing and communication), occurrences of stockout due to a non-anticipatory pharmacy supply chain management, and suboptimal EMR–pharmacy integration that leaves coordination heavily dependent on phone calls and instant messaging. The study concludes that an integrated pharmacy management strategy is required, combining workflow improvement based on Lean–Six Sigma, strengthened supply chain management with a stock early warning system, and accelerated EMR–pharmacy integration within the Hospital Information System (HIS/SIMRS) framework, all supported by effective change management and enhanced human resource capacity.